Health Culture of a Teacher as a Condition and Opportunity for the Implementation of Health-Preserving Behavior in the Educational Environment - Torkachenko Yu.V. (Психолого-педагогические исследования, 2021)
The article actualizes the question of the need to attract the attention of teachers to their own health, as a key condition for the implementation of health-preserving behavior at school. The article presents the results of a study aimed at studying patterns of behavior in the field of health of participants in educational relations. The study involved 84 teachers who took advanced training courses at RSAE SPE “Kamchatka Institute of educational development”, and 570 high school students (grades 9-11) Kamchatka the Region secondary schools. Questionnaires aimed at assessing patterns of behavior in relation to various aspects of health are adapted from the generalized scale of attitudes by I.N. Gurvich, transnational youth health studies (HBSC, ESPAD) and include the following indicators: screen time, use of psychoactive substances, sleep adequacy, eating behavior, physical activity. A comparative analysis of the patterns of behavior of the respondents of both groups was carried out; significant differences were assessed using the angular Fisher transformation. The data obtained is structured in accordance with the research question: are there differences in health-preserving and risky behaviors in the group of teachers and high school students? Taking into account the responsibility imposed by the state on teachers for the formation of a value attitude to health, we assume that in the field of teaching, risky behaviors in relation to various aspects of health are less common than among high school students. Comparative analysis shows that high school students and teachers alike have the same behaviors associated with health risks with regard to tobacco consumption, lack of sleep, and screen time at the computer (gadgets).Considering the fact that the teacher's attitude to his own health is decisive in the professional readiness for the implementation of health-preserving behavior at school, a contradiction arises between the responsibility assigned to the teacher to form a value-based attitude to health and the low culture of the teacher's health. From a practical point of view, the study of behavior patterns in the field of health contributes to the choice of effective ways to prevent ill-being in the school environment, as well as the effective solution of the problems of improving the qualifications of teachers.